Effectiveness Of Implementing The Credit-Module System In Higher Education (Eurasian Journal of Humanities and Social Sciences, 2025)
The article describes the credit-modular education system of students, a system aimed at independent learning and creative mastery of knowledge on the basis of individuality, a system that strictly defines the educational process, choosing an educational path and determining the amount of knowledge in the form of credits, and the urgent importance of using the best experience accumulated in our country and the achievements of foreign countries in organizing education through the credit system for rational examinations. Each of these processes is considered an educational and activity that requires the expenditure and activity of students in accordance with certain labor requirements. It is said that it is important to fairly assess the number of credits based on these factors.